Reducing Disparities for Women and Minority Business in Public Contracting Work: A Call for Social Virtuousness - Murrell, Audrey J.; Bangs, Ralph (Frontiers in Psychology, 2019)
Despite government devoting time and resources to ending discrimination, disparities based on gender, race and disadvantaged business status persist in the area of business development, access to capital and contracting opportunities. We include the concept of virtuousness as part of the need to end disparities and improve social betterment for diverse business enterprise. To that end, our research utilizes critical participatory action research (CPAR) as a tool for building capacity to define and implement meaningful change that has the potential to correct these persistent disparities. We describe a longitudinal project that uses CPAR for addressing gender and racial disparities in local government contracting opportunities. We developed a collaboration with several community, women and minority-serving and legal partners in order to move beyond documenting the problems and toward advancing corrective social policy changes based on the key principles of the CPAR methodology. We described this work in the context of social virtuousness and discuss the implications for future research and public policy.